Analisis Budaya Organisasi terhadap Organizational Citizenship Behavior dengan Employee Engagement sebagai Variabel Mediasi - Satyawati, Cokorda Istri Sri; Rahyuda, Agoes Ganesha (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2022)
The purpose of this study is to find out the effect of organizational culture on OCB mediated by employee engagement at PT. BPD Bali Cabang Utama Denpasar. 76 respondents were used in this study determined with saturated method. Data was collected using a survey approach, where the research instrument used was a questionnaire, then analyzed using the Partial Least Square (PLS). The results showed that organizational culture had a positive significant effect on OCB; Organizational culture has a positive and significant effect on employee engagement; Employee engagement has a positive and significant effect on OCB and Employee engagement able to mediate organizational culture on OCB at PT. BPD Bali Cabang Utama Denpasar.